ANALISA TINGKAT PENGEMBALIAN PEMBIAYAAN BANK SYARIAH YANG LEBIH TINGGI DIBANDINGKAN DENGAN BANK KONVENSIONAL: STUDI KASUS MALAYSIA - Arsyianti, Laily Dwi; Beik, Irfan Syauqi (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2011)
Islamic banking industry has become financial-nerve centre in today’s world economy, particularly in the last three decades. It has attracted various entrepreneurs and enterprises to get its financing. However, Islamic banks tend to have a higher rate of financing compared to the conventional ones. This less competitiveness encourage the demand for Islamic products may fall leaving the Islamic banks. Good debtors opted for conventional loans since the interest rates paid were relatively lower and the rest (the bad debtors) successfully made their way to Islamic banks. Therefore, the non-performing financing of Islamic banks is high. This paper attempts to analyze factors that determine high rate of financing in Islamic banks, by taking the case of Malaysian Islamic banks. In this paper, the top three of Islamic banks and conventional banks are selected for comparison. It finds that high default premium contribute significantly to the high financing rate, while the overheads per capital is no more significantly contribute to it. Hence, the Islamic banks should diversify their assets and implement universal banking concept.